Becoming a Complete Person : Discussing the Aim of Confucian Education - Ma, Wen (Advances in Social Sciences Research Journal, 2020)
The Confucian idea of humanness (Ren) is most commonly translated as “benevolence”. The aim of enhancing one’s virtue such as benevolence is to perform one’s occupation; to position oneself in the world; and to managing the state. Through teaching archery, charioteering(truth), rites(good), and poetry(beauty), the Confucian education aims at cultivate consummate individuals with complete characteristics. The application of Confucian education in the current early childhood education will be discussed.